3T vs. 7T fMRI: capturing early human memory consolidation after motor task utilizing the observed higher functional specificity of 7T - Kreitz, Silke; Mennecke, Angelika; Konerth, Laura; Rösch, Julie; Nagel, Armin Michael; Laun, Frederik Bernd; Uder, Michael; Dörfler, Arnd; Heß, Andreas (Frontiers in Neuroscience, 2023)
Functional magnetic resonance imaging (fMRI) visualizes brain structures at increasingly higher resolution and better signal-to-noise ratio (SNR) as field strength increases. Yet, mapping the blood oxygen level dependent (BOLD) response to distinct neuronal processes continues to be challenging. Here, we investigated the characteristics of 7 T-fMRI compared to 3 T-fMRI in the human brain beyond the effect of increased SNR and verified the benefits of 7 T-fMRI in the detection of tiny, highly specific modulations of functional connectivity in the resting state following a motor task.<br

3T vs. 7T fMRI: capturing early human memory consolidation after motor task utilizing the observed higher functional specificity of 7T - Kreitz, Silke; Mennecke, Angelika; Konerth, Laura; Rösch, Julie; Nagel, Armin Michael; Laun, Frederik Bernd; Uder, Michael; Dörfler, Arnd; Heß, Andreas (Frontiers in Neuroscience, 2023)
Objective: Functional magnetic resonance imaging (fMRI) visualizes brain structures at increasingly higher resolution and better signal-to-noise ratio (SNR) as field strength increases. Yet, mapping the blood oxygen level dependent (BOLD) response to distinct neuronal processes continues to be challenging. Here, we investigated the characteristics of 7 T-fMRI compared to 3 T-fMRI in the human brain beyond the effect of increased SNR and verified the benefits of 7 T-fMRI in the detection of tiny, highly specific modulations of functional connectivity in the resting state following a motor task. Methods: 18 healthy volunteers underwent two resting state and a stimulus driven measurement using a finger tapping motor task at 3 and 7 T, respectively. The SNR for each field strength was adjusted by targeted voxel size variation to minimize the effect of SNR on the field strength specific outcome. Spatial and temporal characteristics of resting state ICA, network graphs, and motor task related activated areas were compared. Finally, a graph theoretical approach was used to detect resting state modulation subsequent to a simple motor task. Results: Spatial extensions of resting state ICA and motor task related activated areas were consistent between field strengths, but temporal characteristics varied, indicating that 7 T achieved a higher functional specificity of the BOLD response than 3 T-fMRI. Following the motor task, only 7 T-fMRI enabled the detection of highly specific connectivity modulations representing an “offline replay” of previous motor activation. Modulated connections of the motor cortex were directly linked to brain regions associated with memory consolidation. Conclusion: These findings reveal how memory processing is initiated even after simple motor tasks, and that it begins earlier than previously shown. Thus, the superior capability of 7 T-fMRI to detect subtle functional dynamics promises to improve diagnostics and therapeutic assessment of neurological diseases.
CRIS-Team Scopus Importer:2023-09-08
Keywords: 7T fMRI; graph theory; memory; motor task; offline replay; resting state

A novel splice variant expands the LAMC3-associated cortical phenotype to frontal only polymicrogyria and adult-onset epilepsy - Kasper, Burkhard; Kraus, Cornelia; Schwarz, Michael; Rösch, Julie; Thiel, Christian; Reis, André; Zweier, Christiane (American Journal of Medical Genetics Part A, 2020)
Bi-allelic loss-of-function variants in LAMC3, encoding extracellular matrix protein laminin gamma 3, represent a rare cause of occipital polymicrogyria with epilepsy, developmental delay and cognitive impairment. So far, only five families have been reported. We now identified a novel, homozygous splice variant in LAMC3 in an individual with an unusual manifestation of cortical malformation. She presented with polymicrogyria in the frontal but not the occipital lobes, with adult-onset seizures and normal psychomotor development and cognition. Additionally, ictal asystole, requiring implantation of a pacemaker, and nonepileptic seizures occurred. This case expands the spectrum of LAMC3-associated cortical malformation phenotypes to frontal only polymicrogyria and adult-onset of epilepsy.
CRIS-Team Scopus Importer:2020-09-18
Keywords: cortical malformation; epilepsy; LAMC3; polymicrogyria; seizures

Brain fMRI Predicts Responses to Certolizumab Pegol in RA. an International, Multi-center, Randomized, Double-blind, Placebocontrolled Trial (PreCePRA) - Rech, Jürgen; Schenker, Hannah; Tascilar, Koray; Hagen, Melanie; Kleyer, Arnd; Simon, David; Mendez, Larissa Valor; Schoenau, Verena; Prade, Jutta; Sergeeva, Marina; Sulvakumar, Mageshvar; Strobelt, Sandra; et al. (ARTHRITIS & RHEUMATOLOGY, 2020)
CRIS-Team WoS Importer:2021-01-15

Brain Structure in Acutely Underweight and Partially Weight-Restored Individuals With Anorexia Nervosa: A Coordinated Analysis by the ENIGMA Eating Disorders Working Group - Walton, Esther; Bernardoni, Fabio; Batury, Victoria Luise; Bahnsen, Klaas; Larivière, Sara; Abbate-Daga, Giovanni; Andres-Perpiña, Susana; Bang, Lasse; Bischoff-Grethe, Amanda; Brooks, Samantha J.; Campbell, Iain C.; Cascino, Giammarco; et al. (Biological Psychiatry, 2022)
Background: The pattern of structural brain abnormalities in anorexia nervosa (AN) is still not well understood. While several studies report substantial deficits in gray matter volume and cortical thickness in acutely underweight patients, others find no differences, or even increases in patients compared with healthy control subjects. Recent weight regain before scanning may explain some of this heterogeneity. To clarify the extent, magnitude, and dependencies of gray matter changes in AN, we conducted a prospective, coordinated meta-analysis of multicenter neuroimaging data. Methods: We analyzed T1-weighted structural magnetic resonance imaging scans assessed with standardized methods from 685 female patients with AN and 963 female healthy control subjects across 22 sites worldwide. In addition to a case-control comparison, we conducted a 3-group analysis comparing healthy control subjects with acutely underweight AN patients (n = 466) and partially weight-restored patients in treatment (n = 251). Results: In AN, reductions in cortical thickness, subcortical volumes, and, to a lesser extent, cortical surface area were sizable (Cohen's d up to 0.95), widespread, and colocalized with hub regions. Highlighting the effects of undernutrition, these deficits were associated with lower body mass index in the AN sample and were less pronounced in partially weight-restored patients. Conclusions: The effect sizes observed for cortical thickness deficits in acute AN are the largest of any psychiatric disorder investigated in the ENIGMA (Enhancing Neuro Imaging Genetics through Meta Analysis) Consortium to date. These results confirm the importance of considering weight loss and renutrition in biomedical research on AN and underscore the importance of treatment engagement to prevent potentially long-lasting structural brain changes in this population.
CRIS-Team Scopus Importer:2022-09-09
Keywords: BMI; Cortical thickness; MRI; Subcortical volume; Surface area

Comparison of Intracranial Aneurysms Treated by 2-D Versus 3-D Coils: A Matched-Pairs Analysis - Lang, Stefan; Rösch, Julie; Gölitz, Philipp; Kloska, Stephan; Struffert, Tobias; Dörfler, Arnd (Clinical Neuroradiology, 2017)
OBJECTIVE: Knowledge on the influence of 2D and 3D coils to occlude intracranial aneurysms is poor. Therefore, aim of our analysis was to evaluate whether the use of 3-D versus 2-D coils alone may improve the efficacy of endovascular aneurysm treatment. PATIENTS AND METHODS: We performed a matched pair analysis comparing aneurysms treated by 3-D coils as initial "framing" coils to aneurysms treated exclusively by 2-D coils. Number of coils, implanted coil length/volume, and associated packing density were calculated. Aneurysmal occlusion was assessed and monitored 6 months (DSA; magnetic resonance angiography (MRA)) and 18 months (MRA) after embolization. Periprocedural complications and retreatment rate of each group were analyzed. RESULTS: Our retrospective analysis revealed 50 pairs. Concerning the 3-D group, number of coils (353 in total, median 7; p = 0.002), implanted coil length (55.69 ± 48.4 cm), implanted coil length per volume (5.92 mm/mm3), and packing density (30 %; p = 0.017) was higher than in the 2-D group (259 in total, median 5 coils; 38.52 ± 43.13 cm; 4.54 mm/mm3; 23 %). Occlusion was not significantly different immediately after treatment but at 6 and 18 months follow-up in favor of 3-D coils. Retreatment was performed in 2 cases of the 3-D group and in 3 cases of the 2-D group and therefore in a similar range (p = 0.564). CONCLUSION: Initial use of 3-D coils revealed a higher packing density and a higher long-term occlusion. Therefore, we recommend initial use of 3-D coils.
EVALuna2:33475

Coregistrating magnetic source and magnetic resonance imaging for epilepsy surgery in focal cortical dysplasia - Kasper, Burkhard; Roessler, Karl; Hamer, Hajo; Dörfler, Arnd; Blümcke, Ingmar; Coras, Roland; Rösch, Julie; Mennecke, Angelika; Wellmer, Joerg; Sommer, Bjoern; Lorber, Bogdan; Lang, Johannes D.; et al. (NeuroImage: Clinical, 2018)
Background: Epilepsy surgery for focal cortical dysplasia type II (FCD II) offers good chances for seizure freedom, but remains a challenge with respect to lesion detection, defining the epileptogenic zone and the optimal resection strategy. Integrating results from magnetic source imaging from magnetoencephalography (MEG) with magnetic resonance imaging (MRI) including MRI postprocessing may be useful for optimizing these goals. Methods: We here present data from 21 adult FCD II patients, investigated during a 10 year period and evaluated including magnetic source imaging. 16 patients had epilepsy surgery, i.e. histopathologically verified FCD II, and a long follow up. We present our analysis of epileptogenic zones including MEG in relation to structural data according to MRI data and relate these results to surgical outcomes. Results: FCD II in our cohort was characterized by high MEG yield and localization accuracy and MEG showed impact on surgical success-rates. MEG source localizations were detected in 95.2% of patients and were as close as 12.3 ± 8,1 mm to the MRI-lesion. After a mean follow up of >3 years, we saw >80% Engel I outcomes, with more favourable outcomes when the MEG source was completely resected (Fishers exact test 0,033). Conclusion: We argue for a high value of conducting a combined MEG-MRI approach in the presurgical workup and the resection strategy in patients with FCD II related epilepsy.
EVALuna2:35523

Diagnostic Performance of 0.55 T MRI for Intracranial Aneurysm Detection - Osmanodja, Filiz; Rösch, Julie; Knott, Michael; Dörfler, Arnd; Grodzki, David; Uder, Michael; Heiß, Rafael (Investigative Radiology, 2023)
OBJECTIVES: Intracranial aneurysm (IA) is the main cause of subarachnoid hemorrhages. Time-of-flight (TOF) magnetic resonance angiography (MRA) at 1.5 T or 3 T magnetic resonance imaging (MRI) is a well-established method for the diagnosis of IA. The aim of this prospective study was to evaluate the performance of a modern 0.55 T MRI in the diagnosis of IAs in comparison to digital subtraction angiography (DSA) as a standard of reference. MATERIALS AND METHODS: Seventeen patients with suspicion of single or multiple IAs underwent TOF MRA at 0.55 T MRI 1 day before DSA. Two neuroradiologists independently measured the aneurysm neck, width, and height on 0.55 T, 1.5 T, and 3 T 3D-TOF MRA source images and 2D/3D rotational angiography. The main analysis assessed the intermodality agreement between 0.55 T TOF MRA and DSA using Bland-Altman plots, a Wilcoxon test, and the intraclass correlation coefficient (ICC). In a secondary analysis, aneurysm dimensions were compared between 0.55 T TOF MRA and 1.5/3 T TOF MRA. Interreader agreement was evaluated by ICC. A third neuroradiologist blinded to patient history screened 0.55 T TOF MRA data sets of the aforementioned 17 patients and 15 additional healthy patients for the presence and location of aneurysms. RESULTS: A total of 19 aneurysms in 16 patients were identified in both 0.55 T MRA and DSA. Measurements of the 2 nonblinded readers showed no significant differences between 0.55 T TOF MRA and DSA in the overall aneurysm size (calculated as the mean from height/width/neck) ( P = 0.178), as well as in the mean width ( P = 0.778) and neck values ( P = 0.190). The mean height was significantly larger in 0.55 T TOF MRA in comparison to DSA ( P = 0.020). Intermodality (1.5/3 T TOF MRA) and interrater agreement were excellent (ICC > 0.94). Of the 32 data sets of patients with and without IA, the blinded reader detected all aneurysms correctly by using 0.55 T images. CONCLUSIONS: TOF-MRA acquired with a modern 0.55 T MRI is a reliable tool for the detection and initial assessment of IAs.
CRIS-Team Scopus Importer:2023-01-20

Impaired maturation of resting-state connectivity in anorexia nervosa from adolescence to adulthood: differential mechanisms of consummatory vs. anticipatory responses through a symptom provocation paradigm - Mendez Torrijos, Andrea; Selvakumar, Mageshwar; Kreitz, Silke; Rösch, Julie; Dörfler, Arnd; Paslakis, Georgios; Krehbiel, Johannes; Steins-Löber, Sabine; Kratz, Oliver; Horndasch, Stefanie; Heß, Andreas (Frontiers in Behavioral Neuroscience, 2024)
This functional magnetic resonance imaging (fMRI) study examined resting-state (RS) connectivity in adolescent and adult patients with anorexia nervosa (AN) using symptom provocation paradigms. Differential food reward mechanisms were investigated through separate assessments of responses to food images and low-caloric/high-caloric food consumption. Thirteen young (≤ 21 years) and seventeen adult (> 21 years) patients with AN and age-matched controls underwent two stimulus-driven fMRI sessions involving RS scans before and after the presentation of food-related stimuli and food consumption. Graph theory and machine learning were used for analyzing the fMRI and clinical data. Healthy controls (HCs) showed widespread developmental changes, while young participants with AN exhibited cerebellum differences for high-calorie food. Young individuals with AN displayed increased connectivity during the consumption of potato chips compared to zucchini, with no differences in adults with AN. Multiparametric machine learning accurately distinguished young individuals with AN from healthy controls based on RS connectivity following food visual stimulation (“anticipatory”) and consumption (“consummatory”). This study highlights the differential food reward mechanisms and minimal developmental changes in RS connectivity from youth to adulthood in individuals with AN compared to healthy controls. Young individuals with AN demonstrated heightened reactivity to high-caloric foods, while adults showed decreased responsiveness, potentially due to desensitization. These findings shed light on aberrant eating behaviors in individuals with AN and contribute to our understanding of the chronicity of the disease.
CRIS-Team Scopus Importer:2024-11-22
Keywords: anorexia nervosa; brain development; fMRI; food intake; graph-theory; machine learning; snack food

Insular Cortical Thickness in Patients With Somatoform Pain Disorder: Are There Associations With Symptom Severity and Childhood Trauma? - Meyer, Elisabeth; Morawa, Eva; Nacak, Yeliz; Rösch, Julie; Dörfler, Arnd; Forster, Clemens; Erim, Yesim (Frontiers in Psychiatry, 2020)
Background: Studies show significant alterations in insular cortical thickness in patients with somatoform pain disorder (SPD). Additionally, associations between childhood maltreatment and morphometric alterations in insular cortex have been observed. Since patients with SPD often report about adverse childhood experiences, we were interested in the interrelationship of exposure to childhood maltreatment and insular cortical thickness in patients with SPD. Methods: Fifteen adult patients with SPD (ICD-10 F 45.40/41, DSM-Code 307.80) and thirteen healthy adult controls underwent T1-weighted MR brain imaging. In the voxel-based morphometry (VBM) analysis we compared whole brain cortical thickness between patients and controls using a Student’s two-sampled t-test (p <.05). Then we performed a secondary analysis to detect differences in cortical thickness levels in the insular cortex between both groups. For further analysis of differences in insular cortical thickness we used gender, age, depressive symptoms [Patient Health Questionnaire (PHQ)-9], and whole brain cortical thickness as nuisance covariates. Subsequently we explored associations between insular cortical thickness, symptom severity (PHQ-15) and past experiences of childhood maltreatment (CTQ) in both groups. Results: Patients showed reduced insular cortical thickness in a subregion of right Brodmann area (BA) 13 (anterior part of the insular cortex), whereas whole brain cortical thickness did not differ between groups. The between-group difference in the identified insular subregion of right BA 13 was not diminished by any of the covariates. This implies that the reduction in cortical thickness in the identified insular subregion might be due to a specific group effect. The effect sizes indicate that the group of patients experienced more childhood maltreatment than the control group. Nonetheless, significant correlations of insular cortical thickness with symptom severity and childhood maltreatment in the total collective could not be demonstrated for the group of patients. Conclusions: Our data suggest that alterations in the identified insular subregion of right BA 13 are associated with somatoform pain, independent of gender, age, or coincident depression levels. To identify significant associations of insular cortical thickness and experiences of childhood maltreatment in patients with SPD investigations within larger samples are highly recommended.
CRIS-Team Scopus Importer:2020-10-02
Keywords: childhood maltreatment; cortical thickness; insula; somatoform pain; voxel-based morphometry

Localization of beta power decrease as measure for lateralization in pre-surgical language mapping with magnetoencephalography, compared with functional magnetic resonance imaging and validated by Wada test - Herfurth, Kirsten; Harpaz, Yuval; Rösch, Julie; Müller, Nadia; Walther, Katrin; Kaltenhaeuser, Martin; Pauli, Elisabeth; Goldstein, Abraham; Hamer, Hajo; Buchfelder, Michael; Dörfler, Arnd; Prell, Julian; et al. (Frontiers in Human Neuroscience, 2022)
Objective: Atypical patterns of language lateralization due to early reorganizational processes constitute a challenge in the pre-surgical evaluation of patients with pharmaco-resistant epilepsy. There is no consensus on an optimal analysis method used for the identification of language dominance in MEG. This study examines the concordance between MEG source localization of beta power desynchronization and fMRI with regard to lateralization and localization of expressive and receptive language areas using a visual verb generation task. Methods: Twenty-five patients with pharmaco-resistant epilepsy, including six patients with atypical language lateralization, and ten right-handed controls obtained MEG and fMRI language assessment. Fourteen patients additionally underwent the Wada test. We analyzed MEG beta power desynchronization in sensor (controls) and source space (patients and controls). Beta power decrease between 13 and 35 Hz was localized applying Dynamic Imaging of Coherent Sources Beamformer technique. Statistical inferences were grounded on cluster-based permutation testing for single subjects. Results: Event-related desynchronization of beta power in MEG was seen within the language-dominant frontal and temporal lobe and within the premotor cortex. Our analysis pipeline consistently yielded left language dominance with high laterality indices in controls. Language lateralization in MEG and Wada test agreed in all 14 patients for inferior frontal, temporal and parietal language areas (Cohen’s Kappa = 1, p < 0.001). fMRI agreed with Wada test in 12 out of 14 cases (85.7%) for Broca’s area (Cohen’s Kappa = 0.71, p = 0.024), while the agreement for temporal and temporo-parietal language areas were non-significant. Concordance between MEG and fMRI laterality indices was highest within the inferior frontal gyrus, with an agreement in 19/24 cases (79.2%), and non-significant for Wernicke’s area. Spatial agreement between fMRI and MEG varied considerably between subjects and brain regions with the lowest Euclidean distances within the inferior frontal region of interest. Conclusion: Localizing the desynchronization of MEG beta power using a verb generation task is a promising tool for the identification of language dominance in the pre-surgical evaluation of epilepsy patients. The overall agreement between MEG and fMRI was lower than expected and might be attributed to differences within the baseline condition. A larger sample size and an adjustment of the experimental designs are needed to draw further conclusions.
CRIS-Team Scopus Importer:2022-11-25
Keywords: beta power decrease; epilepsy; epilepsy surgery; functional magnetic resonance imaging (fMRI); intracarotid sodium amobarbital procedure (IAT); language lateralization; magnetoencephalography (MEG); Wada test

Neural mechanisms of perceptive and affective processing of body stimuli in anorexia nervosa – are there developmental effects? - Horndasch, Stefanie; Rösch, Julie; Kratz, Oliver; Vogel, Anne; Heinrich, Hartmut; Graap, Holmer; Moll, Gunther; Dörfler, Arnd; Forster, Clemens (Psychiatry Research, 2020)
Different components of body image processing seem to be reflected by different neural mechanisms. A core symptom of Anorexia nervosa (AN) is a disturbance of body image with correlates found on a neural level. The present study focuses on the neural processing of visual body stimuli of different weight categories in adolescent and adult AN patients. Thirty-three adolescents aged 12–18 years (15 AN patients, 18 control participants) and 36 adult women (19 AN patients, 17 control participants) underwent functional magnetic resonance imaging (fMRI) while performing a perceptive and an affective body image task involving photographic stimuli of women belonging to different BMI categories. Differential effects on activation, depending on the BMI of the women shown in the pictures, were found in frontal brain regions, the thalamus, the caudate and the fusiform gyrus. Group effects differentiating between AN patients and control participants were seen mainly in the caudate and insula. No significant developmental effect was seen. During a perceptive task, diminished activation of regions involved in perceptive and evaluative functions as well as emotional reasoning was seen in AN. During an affective task there was a tendency towards activation differences reflecting reduced ability of size estimation and impaired integration of visual and body perception with emotions.
CRIS-Team Scopus Importer:2020-03-10
Keywords: Adolescence; Body; Eating disorders; fMRI

Optimized angiographic computed tomography with intravenous contrast injection: An alternative to conventional angiography in the follow-up of clipped aneurysms? Clinical article - Gölitz, Philipp; Struffert, Tobias; Ganslandt, Oliver; Saake, Marc; Lücking, Hannes; Rösch, Julie; Knossalla, Frauke; Dörfler, Arnd (Journal of Neurosurgery, 2012)
Object. The purpose of this study was to evaluate the diagnostic accuracy of an optimized angiographic CT (ACT) program with intravenous contrast agent injection (ivACT) in the assessment of potential aneurysm remnants after neurosurgical clipping compared with conventional digital subtraction angiography (DSA). Methods. The authors report on 14 patients with 19 surgically clipped cerebral aneurysms who were scheduled to undergo angiographic follow-up. For each patient, the authors performed ivACT with dual rotational acquisition and conventional angiography including a 3D rotational run. The ivACT and 3D DSA data were reconstructed with different imaging modes, including a newly implemented subtraction mode with motion correction. Thereafter, the data sets were merged by the dual-volume technique, and freely rotatable 3D images were obtained for further analysis. Observed aneurysm remnants were electronically measured and classified for each modality by 2 experienced neuroradiologists. Results. Digital subtraction angiography and ivACT both provided high-quality images without motion artifacts. Artifact disturbances from the aneurysm clips led to a compromised, but still sufficient, image quality in 1 case. The ivACT assessed all aneurysm remnants as true-positive up to a minimal size of 2.6 x 2.4 mm in accordance with the DSA findings. There was a tendency for ivACT to overestimate the size of the aneurysm remnants. All cases without aneurysm remnants on DSA were scored correctly as true-negative by ivACT. Conclusions. By using an optimized image acquisition protocol as well as enhanced postprocessing algorithms, the noninvasive ivACT seems to achieve results comparable to those of conventional angiography in the follow-up of clipped cerebral aneurysms. The authors have shown that ivACT can provide reliable diagnostic information about potential aneurysm remnants after neurosurgical clipping with high sensitivity and specificity, sufficient for clinical decision making, at least for aneurysms in the anterior circulation located distal to the internal carotid artery. These preliminary results may be a promising step to replace conventional angiography by a noninvasive imaging technique in selected cases after aneurysm clipping.
CRIS-Team Scopus Importer:2022-08-05
Keywords: Aneurysm clipping; Angiographic computed tomography; Follow-up imaging; Noninvasive imaging; Vascular disorders

Prediction of Response to Certolizumab-Pegol in Rheumatoid Arthritis By Functional MRI of the Brain - an Interim Analysis of an Ongoing Investigator Initiated Phase III Trial - Schenker, Hannah; Heß, Andreas; Konerth, Laura; Sergeeva, Marina; Prade, Jutta; Kleyer, Arnd; Reiser, Michaela; Hueber, Axel; Englbrecht, Matthias; Feist, Eugen; Voll, Reinhard; Bannert, Bettina; et al. (2017)
EVALuna2:33139

Quiet diffusion-weighted head scanning: Initial clinical evaluation in ischemic stroke patients at 1.5T - Rösch, Julie; Ott, Martin; Heismann, Bjoern; Dörfler, Arnd; Engelhorn, Tobias; Sembritzki, Klaus; Grodzki, David M. (Journal of Magnetic Resonance Imaging, 2016)
PURPOSE: To compare the quality and diagnostic value of routine single-shot, echo-planar imaging, diffusion-weighted imaging (ss-EPI-DWI) to those of quiet readout segmented EPI-DWI (q-DWI) in magnetic resonance imaging (MRI) of acute stroke. MATERIALS AND METHODS: Twenty-six patients with acute stroke underwent a 1.5T MRI including diffusion-weighted ss-EPI and q-DWI. The two sequences were protocolled to have identical spatial resolution and spatial coverage. q-DWI was tested with (regular q-DWI) and without (fast q-DWI) averaging in 13 patients each. The acoustic noise generated by each sequence was measured. Quantitative and qualitative assessments regarding signal-to-noise ratio (SNR), contrast-to-noise ratio (CNR), lesion conspicuity, level of artifacts, overall image quality as well as diagnostic content were performed. RESULTS: SNR and CNR values of the q-DWI scans were considerably higher than those of ss-EPI DWI (P ≤ 0.0078). No statistical difference was found for lesion conspicuity (P ≥ 0.125). Statistical differences were found for level of artifacts (P ≥ 0.0078) and overall image quality (P ≥ 0.002). Both were evaluated better in the ss-EPI DWI than in the regular and fast q-DWI. Apart from one fast q-DWI patient, radiologists voted the images to have the same diagnostic content, with upper 90% confidence limits of 0.238 for regular q-DWI and 0.429 for fast q-DWI. CONCLUSION: If the acoustic burden is critical to the patient, q-DWI is an equivalent quiet alternative to ss-EPI DWI for use in stroke patients. J. Magn. Reson. Imaging 2016;44:1238-1243.
EVALuna2:33143

Quiet FLAIR at 7T MRI - Rösch, Julie; Mennecke, Angelika; Knott, Michael; Dörfler, Arnd; Grodzki, David M. (Investigative Radiology, 2020)
OBJECTIVE: The aim of this study was to investigate acoustic noise reduction and image quality of cranial magnetic resonance imaging (MRI) at 7T MRI with and without sequence-based acoustic noise reduction. MATERIALS AND METHODS: Fifteen patients and 5 healthy volunteers underwent 7T MRI scanning. A fluid-attenuated inversion recovery (FLAIR) sequence was acquired with and without sequence-based acoustic noise reduction. The acoustic noise generated by each sequence was measured. Quantitative and qualitative assessments regarding signal-to-noise ratio, contrast-to-noise ratio, lesion conspicuity, level of artifacts, and overall image quality were performed. Furthermore, detection rates of white matter lesions were evaluated by 2 observers for both sequences. RESULTS: Acoustic noise was significantly reduced from initially 92.7 dB(A) to 78.9 dB(A), corresponding to an 80% reduction in sound pressure. The visual assessment revealed no significant difference in the level of artifacts. Although rated very high by both readers, lesion conspicuity and image quality averaged better for the regular FLAIR sequence. Signal-to-noise ratio and contrast-to-noise ratio slightly decreased when applying the sequence-based acoustic noise reduction. No significant difference was found between the detection rates of white matter lesions for both observers. CONCLUSIONS: Reducing sound pressure by 80% in FLAIR imaging at 7T ultra-high-field MRI is feasible while maintaining high diagnostic image quality.
CRIS-Team Scopus Importer:2020-10-23

Resection of dominant fusiform gyrus is associated with decline of naming function when temporal lobe epilepsy manifests after the age of five: A voxel-based lesion-symptom mapping study - Reindl, Caroline; Allgäuer, Andrea; Kleiser, Benedict; Onugoren, Müjgan Dogan; Lang, Johannes; Welte, Tamara; Stritzelberger, Jenny; Winder, Klemens; Schwarz, Michael; Gollwitzer, Stephanie; Trollmann, Regina; Rösch, Julie; et al. (NeuroImage: Clinical, 2022)
Objective: To determine patients’ characteristics and regions in the temporal lobe where resections lead to a decline in picture naming. Methods: 311 patients with left hemispheric dominance for language were included who underwent epilepsy surgery at the Epilepsy Center of Erlangen and whose picture naming scores (Boston Naming Test, BNT) were available preoperatively and 6-months postoperatively. Surgical lesions were mapped to an averaged template based on preoperative and postoperative MRI using voxel-based lesion-symptom mapping (VBLSM). Postoperative brain shifts were corrected. The relationship between lesioned brain areas and the presence of a postoperative naming decline was examined voxel-wise while controlling for effects of overall lesion size at first in the total cohort and then restricted to temporal lobe resections. Results: In VBLSM in the total sample, a decline in BNT score was significantly related to left temporal surgery. When only considering patients with left temporal lobe resections (n = 121), 40 (33.1%) significantly worsened in BNT postoperatively. VBLSM including all patients with left temporal resections generated no significant results within the temporal lobe. However, naming decline of patients with epilepsy onset after 5 years of age was significantly associated with resections in the left inferior temporal (extent of BNT decline range: 10.8− 14.4%) and fusiform gyrus (decline range: 12.1−18.4%). Significance: Resections in the posterior part of the dominant fusiform and inferior temporal gyrus was associated with a risk of deterioration in naming performance at six months after surgery in patients with epilepsy onset after 5 years of age but not with earlier epilepsy onset.
CRIS-Team Scopus Importer:2022-08-19
Keywords: Basal temporal language area; Epilepsy surgery; Gyrus fusiformis; Lesion localization; Naming; Neuropsychological outcome

Snack food as a modulator of human resting-state functional connectivity. - Mendez Torrijos, Andrea; Kreitz, Silke; Ivan, Claudiu-Ionut; Konerth, Laura; Rösch, Julie; Pischetsrieder, Monika; Moll, Gunther; Kratz, Oliver; Dörfler, Arnd; Horndasch, Stefanie; Hess, Andreas (Cns Spectrums, 2018)
OBJECTIVE To elucidate the mechanisms of how snack foods may induce non-homeostatic food intake, we used resting state functional magnetic resonance imaging (fMRI), as resting state networks can individually adapt to experience after short time exposures. In addition, we used graph theoretical analysis together with machine learning techniques (support vector machine) to identifying biomarkers that can categorize between high-caloric (potato chips) vs. low-caloric (zucchini) food stimulation. METHODS Seventeen healthy human subjects with body mass index (BMI) 19 to 27 underwent 2 different fMRI sessions where an initial resting state scan was acquired, followed by visual presentation of different images of potato chips and zucchini. There was then a 5-minute pause to ingest food (day 1=potato chips, day 3=zucchini), followed by a second resting state scan. fMRI data were further analyzed using graph theory analysis and support vector machine techniques. RESULTS Potato chips vs. zucchini stimulation led to significant connectivity changes. The support vector machine was able to accurately categorize the 2 types of food stimuli with 100% accuracy. Visual, auditory, and somatosensory structures, as well as thalamus, insula, and basal ganglia were found to be important for food classification. After potato chips consumption, the BMI was associated with the path length and degree in nucleus accumbens, middle temporal gyrus, and thalamus. CONCLUSION The results suggest that high vs. low caloric food stimulation in healthy individuals can induce significant changes in resting state networks. These changes can be detected using graph theory measures in conjunction with support vector machine. Additionally, we found that the BMI affects the response of the nucleus accumbens when high caloric food is consume
Keywords: Food intake; graph theory; resting state networks; RS-fMRi; snack food; support vector machine

Surgical planning, histopathology findings and postoperative outcome in MR-negative extra-temporal epilepsy using intracranial EEG, functional imaging, magnetoencephalography, neuronavigation and intraoperative MRI. - Maslarova, Anna; Zhao, Yining; Rösch, Julie; Dörfler, Arnd; Coras, Roland; Blümcke, Ingmar; Lang, Johannes; Schmidt, Manuel; Hamer, Hajo; Reindl, Caroline; Welte, Tamara; Rampp, Stefan; et al. (Clinical Neurology and Neurosurgery, 2023)
OBJECTIVE: MRI-negative drug-resistant epilepsy presents a challenge when it comes to surgical planning, and surgical outcome is worse than in cases with an identified lesion. Although increasing implementation of more powerful MRI scanners and artificial intelligence has led to the detection of previously unrecognizable lesions, in some cases even postoperative pathological evaluation of electrographically epileptogenic zones shows no structural alterations. While in temporal lobe epilepsy a standardized resection approach can usually be performed, the surgical management of extra-temporal lesions is always individual. Here we present a strategy for treating patients with extra-temporal MRI-negative epilepsy focus and report our histological findings and patient outcome. METHODS: Patients undergoing epilepsy surgery in the Department of Neurosurgery at the University Hospital Erlangen between 2012 and 2020 were included in the study. Inclusion criteria were: (1) failure to identify a structural lesion on preoperative high-resolution 3 Tesla MRI with a standardized epilepsy protocol and (2) preoperative intracranial EEG (iEEG) diagnostics. RESULTS: We identified 8 patients corresponding to the inclusion criteria. Second look MRI analysis by an experienced neuroradiologist including the most recent analysis algorithm utilized in our clinic revealed a possible lesion in two patients. One of the patients with a clear focal cortical dysplasia (FCD) finding on a second look was excluded from further analysis. Of the other 7 patients, in one patient iEEG was performed with subdural electrodes, whereas the other 6 were evaluated with depth electrodes. MEG was performed preoperatively in all but one patient. An MEG focus was implemented in resection planning in 3 patients. FDG PET was performed in all, but only implemented in one patient. Histopathological evaluation revealed one non-lesional case, 4 cases of FCD and 2 cases with mild developmental malformation. All patients were free from permanent neurological deficits and presented with Engel 1A or 1B outcome on the last follow-up. CONCLUSION: We demonstrate that extra-temporal MRI-negative epilepsy can be treated successfully provided an extensive preoperative planning is performed. The most important diagnostic was stereo-EEG, whereas additional data from MEG was helpful and FDG PET was rarely useful in our cohort.
EVALuna2:522951

Symmetric tract-based spatial statistics of patients with left versus right mesial temporal lobe epilepsy with hippocampal sclerosis - Mennecke, Angelika; Rösch, Julie; Kasper, Burkhard; Schmidt, Manuel; Roessler, Karl; Coras, Roland; Hamer, Hajo; Dörfler, Arnd; Laun, Frederik Bernd (NeuroReport, 2018)
This study aims to investigate the diffusion metrics of left versus right temporal lobe epilepsy in a well-defined subgroup of patients with mesial temporal lobe epilepsy (mTLE) because of unilateral hippocampal sclerosis while taking into account interhemispheric differences. Eighteen patients with TLE [nine left temporal lobe epilepsy (LTLE) and nine right temporal lobe epilepsy (RTLE)] and a norm group of 36 nonepileptic individuals were scanned with a multiband accelerated diffusion tensor imaging protocol at 3T. The scalar diffusion tensor parameters fractional anisotropy (FA), mean diffusivity (MD), and radial diffusivity (RD) and, after projection on a symmetric skeleton, their hemispheric difference (dFA, dMD, and dRD) were analyzed using tract-based spatial statistics. In the cluster with significantly (P<0.008) different dFA, dMD, and dRD between right TLE and left TLE, the hemispheric difference in the mean scalar indices (dmFA, dmMD, and dmRD) was assessed and tested for differences using a one-way analysis of variance and for correlation with patient age, seizure onset, or duration of epilepsy using Pearson's correlation. Patients with LTLE showed lower dFA, higher dMD, and higher dRD (P<0.008) compared with patients with RTLE in a cluster including parts of the uncinated and inferior longitudinal fasciculus and the inferior fronto-occipital fasciculus. dmFA, dmMD, and dmRD differed significantly between groups (P<10, corrected) and showed no correlation with patient age, seizure onset, or duration of epilepsy. The exclusion of bilateral interindividual variance through the calculation of the hemispheric difference of the diffusion metrics by the symmetric variant of tract-based spatial statistics allows for a sensitive differentiation of LTLE and RTLE with unilateral hippocampal sclerosis.
EVALuna2:34910

T2-sequence with contrast inversion: diagnostic value in the investigation of gray matter heterotopias - Rösch, Julie; Mennecke, Angelika; Knott, Michael; Hamer, Hajo; Dörfler, Arnd; Engelhorn, Tobias Martin (NeuroReport, 2020)
To compare the diagnostic value of T1-inversion recovery sequence (T1 IR) to that of a T2-sequence with contrast inversion (T2 CI) in the investigation of heterotopias. In this study, we processed a contrast-inverted copy of our coronal T2-sequence of 21 patients with subependymal and subcortical heterotopias on an online picture archiving and communication system workstation. The diagnostic performance of these images was compared with the T1 IR of the same patients by quantitative and qualitative assessments regarding signal-to-noise ratio (SNR), lesion-to-white matter contrast-to-noise ratio (CNR), lesion conspicuity, level of artifacts, overall image quality as well as diagnostic content. SNR values of the T2 CI were significantly higher than those of the T1 IR. CNR values of both sequences were similar. No relevant difference was found for lesion conspicuity and level of artifacts. Overall image quality of the T2 CI was rated slightly better by one reader. Both readers voted the images to have the same diagnostic content. Beside the exact depiction of the hippocampus in the high resoluted T2-sequence, its contrast-inverted copy (T2 CI) is also useful in the detection of heterotopias. In conjunction with the MPRAGE or MP2RAGE as a three-dimensional sequence, it could offer an equivalent and time-saving alternative to the T1 IR in the investigation of this type of malformation of cortical development.
CRIS-Team Scopus Importer:2020-05-29

Ultra-early Detection of Microcirculatory Injury as Predictor of Developing Delayed Cerebral Ischemia After Aneurysmal Subarachnoid Hemorrhage - Gölitz, Philipp; Rösch, Julie; Roessler, Karl; Knossalla, Frauke; Dörfler, Arnd; Hölter, Philip (Clinical Neuroradiology, 2018)
Purpose Delayed cerebral ischemia (DCI) still remains amajor complication after subarachnoid hemorrhage (SAH). The aim of our study was to evaluate whether flow analysis of admission digital subtraction angiography (DSA) using parametric color coding (PCC), apostprocessing algorithm, allows ultra-early identification of SAH patients at risk for developing subsequent symptomatic vasospasm. Methods In this study 52patients who suffered SAH from aneurysm rupture, were retrospectively enrolled. Of the patients 26 developed DCI and angiographically proven cerebral vasospasm and 26age, gender-and clinical status-matched SAH patients without DCI served as controls. Using PCC, the following flow parameters were calculated: cerebral circulation time (CirT), cortical relative time to peak (rTTP) and microvascular transit time (TT). Results Mean cerebral CirT and cortical rTTP were longer in the DCI group (6.42s +/- 1.54 and 3.16s +/- 0.86, respectively) than in the non-DCI group (5.77s +/- 1.86 and 3.11s +/- 1.41, respectively), but without statistical significance. The mean microvascular TT was statistically significantly (p = 0.04) longer in the DCI group (3.19s +/- 0.78) than in the non-DCI group (2.67s +/- 0.73). Conclusion Angiographic flow analysis might be suitable for ultra-early detection and quantitative assessment of microcirculatory injury in SAH patients, predictive of developing subsequent DCI. Prolonged microvascular TT seems to be asignificant independent factor positively associated with DCI development. Identifying SAH patients at risk for DCI ultra-early after ictus might contribute to initiate prophylactic therapies before clinical deterioration.
EVALuna2:34933

Value of Flat-detector Computed Tomography Angiography with Intravenous Contrast Media Injection in the Evaluation and Treatment of Acutely Ruptured Aneurysms of the AcomA complex: A Single Center Experience in 15 Cases - Rösch, Julie; Lang, Stefan; Gölitz, Philipp; Kallmünzer, Bernd; Roessler, Karl; Dörfler, Arnd; Struffert, Tobias (Clinical Neuroradiology, 2018)
Objective To illustrate the added value of flat-detector computed tomography angiography with intravenous contrast media injection (intravenous FDCTA) in the evaluation of complex A1/A2/AcomA aneurysms. Patients and Methods We retrospectively reviewed 15patients with ruptured aneurysms. In each patient, an intravenous FDCTA was performed and its diagnostic value investigated. Results In all patients, FDCTA contributed relevant additional information concerning the anatomy of the A1/A2/AcomA complex and the relationship of the aneurysm neck to these vascular structures, which could not be gained by 2D- and 3D-DSA, and changed the management in 33% of the patients (5 out of 15). In an additional 5cases, knowledge of the detailed anatomy was helpful to plan the exact stent position. Conclusion In case of complex A1/A2/AcomA aneurysms, intravenous FDCTA is an effective option to visualize the exact location of the aneurysm neck and the relationship between the aneurysm and the adjacent vessels. Thus, it is of significant added value in the precise planning of atherapeutic strategy.
EVALuna2:34934